GANGGUAN SATWA LIAR DI SEKITAR SUAKA MARGASATWA BUKIT RIMBANG BUKIT BALING STUDI KASUS DESA PETAI DAN DESA PULAU PADANG KABUPATEN KUANTAN SINGINGI - Syafathisca Syafathisca; Defri Yoza; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Wildlife is one of the biodiversity in Indonesia which is partially disturbed by its existence and habitat by human activity which continues to increase every year. Conflict between humans and wildlife occurs as a result of a number of negative interaction both direct and indirect between humans and wildlife. The purpose of this study was to determine the form and types of wilflife disturbance and the factors that cause wildlife conflicts that often enter the community agricultural land around the Bukit Rimbang Bukit Baling Wildlife Reserve. This research was contucted on March 2020. The object if this research is the people who have agricultural land around the Bukit Rimbang Bukit Baling Wildlife Reserve. Based on the results of research on the forms and types of wildlife disturbance to community agricultural land, namely destroying crops, destroying community huts, attacking community, destroying land and destroying root. The cause of wildlife conflicts that often enter community agricultural lands are habitat destruction due to encroachment, increasing population and animal preferences for plant species. Keywords :Wildlife Disturbance, Community agriculturalland, SMBRBB Keywords :Wildlife Disturbance, Community agriculturalland, SMBRBB